1992
DOI: 10.1520/jte11726j
|View full text |Cite
|
Sign up to set email alerts
|

Podometrics: A New Methodology for Foot Typing

Abstract: Podometrics is an original and innovative system to establish cartographical and geometrical parameters for the human foot: a methodology for “mapping” the foot to determine foot types by anthropometrical classification. A methodology has long been evasive because of the challenging complexities of the foot with its unique shapes, components and many converging contours and angles. Foot typing efforts to date have not been particularly productive or effective because the emphasis has been mostly on external fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Rossi described a method which he called his Podometric System that could be used by clinicians, rather than forensic practitioners, to describe foot types through categorising key landmarks of the foot and their relationship to each other. 9 Rossi's system was based on the placement of five longitudinal lines and five lateral lines through prescribed positions relative to the plantar surface of the foot with each set of lines converging at a central point (Figure 4). Although Rossi did not envisage his methods to be used in the forensic evaluation of footprints, those working in the field of footprints saw this approach as having the potential to be utilised, 89 although to date his methods do not appear to have been tested and used in practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rossi described a method which he called his Podometric System that could be used by clinicians, rather than forensic practitioners, to describe foot types through categorising key landmarks of the foot and their relationship to each other. 9 Rossi's system was based on the placement of five longitudinal lines and five lateral lines through prescribed positions relative to the plantar surface of the foot with each set of lines converging at a central point (Figure 4). Although Rossi did not envisage his methods to be used in the forensic evaluation of footprints, those working in the field of footprints saw this approach as having the potential to be utilised, 89 although to date his methods do not appear to have been tested and used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…For their previously described large-scale study investigating the uniqueness of the human footprint, Kennedy et al later devised a measurement approach which included a central axis to align each footprint vertically for analysis. 14,15 Reel et al 18 adopted this central axis approach by utilizing the inner and outer tangent lines of the footprint 9 with incorporation of Gunn lines ( Figure 5). Rather than drawing and recording measurements manually, Reel et al demonstrated high reliability using automated GNU Image Manipulation Program software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation